Analyzing Legislative Approaches to the Rehabilitation of Drug Addicts through a Social Engineering Lens: Best Practices and Challenges - Ngaisah, Siti; Widoyoko, Wredha Danang; Haryono, Haryono; Rahmawati, Diah Ayu; Prayogi, Yoga Adi (West Science Interdisciplinary Studies, 2024)
This study analyzes legislative approaches to the rehabilitation of drug addicts through the lens of social engineering, examining best practices and identifying key challenges. A juridical analysis of selected national and international legislation highlights the alignment of legal frameworks with social engineering principles, focusing on recovery, reintegration, and harm reduction. Case studies from jurisdictions like Portugal and the Netherlands demonstrate the effectiveness of decriminalization and integrated healthcare policies in reducing recidivism and improving public health. However, challenges such as resource constraints, societal stigma, and policy inconsistencies remain significant barriers to implementation. The findings emphasize the need for comprehensive, evidence-based legislation that balances punitive and rehabilitative measures to address drug addiction effectively.
Keywords: Drug Rehabilitation; Social Engineering; Legislative Framework; Harm Reduction